Investigation of the effect of thermal residual stresses on deformation of α-uranium through neutron diffraction measurements and crystal plasticity modeling. (15th February 2015) - Calhoun, C.A.; Garlea, E.; Mulay, R.P.; Sisneros, T.A.; Agnew, S.R.
Abstract: The strong thermoelastic–plastic anisotropy of single crystal, orthorhombic α-uranium leads to the generation of significant thermal residual stresses (TRSs) after cooling from the processing temperatures of polycrystals. The present study shows the effect that these TRSs have upon subsequent room temperature deformation after aging. In situ neutron diffraction strain experiments performed on specimens machined from a clock-rolled plate, combined with ex situ texture measurements and elastoplastic self-consistent polycrystalline plasticity modeling, provides the necessary information to quantify the relative strengths and activities of the various deformation mechanisms known to operate within α-uranium. The results demonstrate that the activation of hard slip modes is necessary in order to generate macroscopic flow at the stress levels observed experimentally. Although the thermal residual stresses do not drastically affect the "bulk" response, inclusion of the TRSs drastically improve the agreement between predicted and experimentally measured internal strain evolution and strongly alter the predicted slip and twinning mode activities. As such, modeling efforts to discern the roles of the various mechanisms must account for the presence of thermal residual stress. In agreement with prior crystal plasticity modeling efforts, the crystallographic texture and polarity of twinning mechanisms explain the tension–compression strength asymmetry observed in the material (i.e. significantly more of the soft {1 3 0} twinning mode is observed to occur during compression along the prior plate RD than tension along the same direction).